The IoT Architect's Guide to Attainable Security and Privacy - Fagbemi, Damilare D (Auerbach Publications, 2019)
This book explores how to secure the future state of the Internet of Things. Looking at an imminent future filled with computers that also moonlight as "things", the guide dissect the present and future threats to assets, digital and other wise. To avoid the significant technical debt which is likely to manifest as IoT adoption increases, it's important to think ahead. To that effect, the book examines how to design IoT solutions that provide end-to-end security and privacy at scale, delves into IoT economy from the perspective of both defenders and attackers, and discusses the implications of security usability.